2007
DOI: 10.1212/01.wnl.0000278109.76607.0a
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor integration is abnormal in asymptomatic Parkin mutation carriers

Abstract: The relative decrease in sensorimotor inhibition may be a direct consequence of the Parkin mutation or represent adaptive changes at the cortical level in response to a subcortical dysfunction, but is not caused by motor symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Thresholds are usually normal in PD and, if altered, they tend to be low 15. Thresholds were also normal in the study by Baumer et al17; however their cohort was on average 20 years younger than ours (66.5 ± 3.4 years in our study vs. 40 ± 1.2 in the study17). If these younger carriers were to be tested 20 years later, it may be found that their thresholds have increased.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Thresholds are usually normal in PD and, if altered, they tend to be low 15. Thresholds were also normal in the study by Baumer et al17; however their cohort was on average 20 years younger than ours (66.5 ± 3.4 years in our study vs. 40 ± 1.2 in the study17). If these younger carriers were to be tested 20 years later, it may be found that their thresholds have increased.…”
Section: Discussionsupporting
confidence: 47%
“…Electrophysiological studies of carriers are also limited. A recent report17 found abnormal short afferent inhibition (SAI), a measure of sensorimotor integration and cholinergic activity, whereas short interval intracortical inhibition (SICI), mediated mainly by GABA A interneurons, was normal 18. However, it was unclear whether this was a form of “compensation” or a direct consequence of the underlying dopaminergic deficit.…”
mentioning
confidence: 99%
“…So far, TMS has only been used to assess excitability changes in sensorimotor circuits. 42 In the context of functional reorganization, TMS may also be used to transiently disrupt task-related processing in motor cortical areas that show compensatory activity. This would allow estimating the functional relevance of these areas for the maintenance of a motor function.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed sensory-driven compensatory mechanisms in cortico-thalamo-cortical circuits (Bezard et al, 2003;Escola et al, 2003;Pessiglione et al, 2003), but it remains unclear to what extent these animal models can be generalized to human Parkinson's disease. More recently, neuroimaging studies in non-manifesting carriers of mutations known to cause monogenetic forms of Parkinson's disease, such as Parkin (PARK2) or PINK1 (PARK6) mutations (Broussolle et al, 2000;Hilker et al, 2001;Khan et al, 2002aKhan et al, , b, 2005bWalter et al, 2004;Buhmann et al, 2005;Baumer et al, 2007;Binkofski et al, 2007;Hagenah et al, 2007Hagenah et al, , 2008Schweitzer et al, 2007;van Nuenen et al, 2009a, b;Reetz et al, 2010;Saunders-Pullman et al, 2010), have been used to map cerebral changes occurring before the clinical onset of Parkinson's disease (Farrer, 2006). Non-manifesting carriers of these mutations showed structural and functional alterations similar to those observed in idiopathic Parkinson's disease, for example, nigrostriatal and premotor dysfunctions.…”
Section: Introductionmentioning
confidence: 99%